The Gut–Kidney Axis in Chronic Kidney Diseases - Kenji Tsuji; Naruhiko Uchida; Hiroyuki Nakanoh; Kazuhiko Fukushima; Soichiro Haraguchi; Shinji Kitamura; Jun Wada (Diagnostics)
The gut–kidney axis represents the complex interactions between the gut microbiota and kidney, which significantly impact the progression of chronic kidney disease (CKD) and overall patient health. In CKD patients, imbalances in the gut microbiota promote the production of uremic toxins, such as indoxyl sulfate and p-cresyl sulfate, which impair renal function and contribute to systemic inflammation. Mechanisms like endotoxemia, immune activation and oxidative stress worsen renal damage by activating pro-inflammatory and oxidative pathways. Insights into these mechanisms highlight the impact of gut-derived metabolites, bacterial translocation, and immune response changes on kidney health, suggesting new potential approaches for CKD treatment. Clinical applications, such as dietary interventions, prebiotics, probiotics and fecal microbiota transplantation, are promising in adjusting the gut microbiota to alleviate CKD symptoms and slow disease progression. Current research highlights the clinical relevance of the gut–kidney axis, but further study is essential to clarify these mechanisms’ diagnostic biomarkers and optimize therapeutic interventions. This review emphasizes the importance of an integrated approach to CKD management, focusing on the gut microbiota as a therapeutic target to limit kidney injury.